Pelatihan E-Learning Berbasis Web Blog Bagi Guru SD - Sujarwo Sujarwo; Leo Charli; Rani Okta Felani (LP4MK STKIP PGRI Lubuklinggau, 2025)
In the current digital era, the use of science and technology is a must for educators. Technology, information and communication (ICT)-based learning innovation is one of the important things to be implemented in educational units. Therefore, it is very important to increase the ability of human resources to use ICT, starting from skills and knowledge, planning, operation, maintenance and supervision, as well as increasing ICT capabilities in various agencies, especially in the education sector. Educators have a main role so they must continue to learn to improve their competence, because the students they face are the generation born in the current digital era. The development of ICT has given rise to various new applications as a means of learning, known as e-learning. E-learning is the basis and logical consequence of the development of information and communication technology. E-learning is part of a system that can simplify the teaching and learning process by utilizing online media. Based on the results of the TEAM's observations at SD Negeri Purwara V, Kelumpang Jaya Village, it was found that the majority of elementary school teachers did not have skills in the field of technology, especially in creating e-learning. Teachers' limited knowledge in managing technology for e-learning is one of the obstacles teachers face. So far, teachers have only carried out the learning process using textbooks and have not used technology-assisted learning media. The condition of the teachers at SD Negeri Purwara V, Kelumpang Jaya Village, Nibung District, most of whom do not know how to manage technology into e-learning and can be used as a learning medium, so there is a need to update scientific and technological information, namely by holding e-learning outreach and training web-based blog. With e-learning, it is hoped that teachers can further develop learning media which in the end can improve student learning outcomes and improve the quality of human resources in elementary schools. The aim of this Community Service is to provide education and practice in creating web blogs for Purwara V State Elementary School teachers. The method of implementing activities is divided into four stages, namely, the preparation stage, the training stage, the implementation stage and the evaluation stage. The service activities carried out for teachers at SD N Purwara V have gone well. This can be seen from the very high enthusiasm of teachers in participating in training activities. This indicates that the teachers responded positively to the activities that had been carried out. In accordance with the school's expectations, they really hope that there will be activities that provide refreshment for teachers at SD N Purwara V, both related to deepening study material and related to teaching methods and learning media. The principal and teachers enthusiastically welcomed the implementation of this activity and hoped that the implementation of the activity could be carried out continuously to help improve the quality of teachers in the elementary school. The principal also hopes that there will be similar activities specifically to guide teachers in implementing the creation of other media that can be used for the classroom learning process. In training activities, the teachers were very enthusiastic in practicing the science and technology-based learning media that had been prepared. Thus, this service activity has gone well